2014
DOI: 10.1016/j.cortex.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Deriving semantic structure from category fluency: Clustering techniques and their pitfalls

Abstract: Assessing verbal output in category fluency tasks provides a sensitive indicator of cortical dysfunction. The most common metrics are the overall number of words produced and the number of errors. Two main observations have been made about the structure of the output, first that there is a temporal component to it with words being generated in spurts, and second that the clustering pattern may reflect a search for meanings such that the ‘clustering’ is attributable to the activation of a specific semantic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Specifically, the recall process likely involves a search for meanings as reflected in the ‘clustering’ of words in the output. Many approaches have been employed to examine the structure of the clustering, but are often problematic given the subjective judgments of cluster boundaries or have turned out to be simply unreliable (Voorspoels et al, 2013, in press). We have previously adopted LSA as an objective and reliable methodology to chart the flow of meaning in words and discourse (Elvevåg et al, 2007), and briefly describe this technique below.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the recall process likely involves a search for meanings as reflected in the ‘clustering’ of words in the output. Many approaches have been employed to examine the structure of the clustering, but are often problematic given the subjective judgments of cluster boundaries or have turned out to be simply unreliable (Voorspoels et al, 2013, in press). We have previously adopted LSA as an objective and reliable methodology to chart the flow of meaning in words and discourse (Elvevåg et al, 2007), and briefly describe this technique below.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that both factors independently affect verbal fluency function. A successive study failed to replicate the findings as it found no essential differences between schizophrenia patients and healthy controls in terms of cluster size, regardless of verbal fluency type (Voorspoels et al, 2014). Not only the number of clusters, but also their internal structure is analysed, which means examination of features such as distinction (how semantically different the clusters are), inclusion (a larger cluster can contain several smaller ones) and how overriding they are (parent cluster contains several smaller clusters).…”
Section: Or Ruff Figural Fluencymentioning
confidence: 56%
“…Compared to healthy controls, results for schizophrenia patients showed differences in the number of generated words. However, the number of clusters, their quality and the frequency of switching between clusters or between clusters and words did not change (Voorspoels et al, 2014). Decreased speed of information processing was demonstrated to affect the number of generated words in the investigated group of patients (Hong et al, 2002;Riley et al, 2000;van Beilen et al, 2004;Vinogradov et al, 2003).…”
Section: Or Ruff Figural Fluencymentioning
confidence: 92%
“…These findings were similar to the previous study by these researchers, in which there was no correlation between total evoked words and auditory characteristics of the subjects 1 . Another recent study hypothesized that although there may be quantitative differences in recalled words, the qualitative aspect of lexical organization does not change in different pathologies 26 .…”
Section: Discussionmentioning
confidence: 99%